PENINGKATAN HASIL BELAJAR SISWA MELALUI MODEL BRAIN BASED LEARNING BERBANTUAN MEDIA BARANG BEKAS PADA MATERI PENGUMPULAN DAN PENYAJIAN DATA KELAS V SDN KEPATIHAN - Nuriyatul Fadhilah; Rintis Rizkia Pangestika; Nurhidayati (LPPM Universitas Cipta Mandiri, 2024)
Mastery of mathematical material by students is a non-negotiable necessity in structuring reasoning and decision making in the current era of increasingly competitive competition. In other words, mathematics has a very essential role for other sciences, the main ones being science and technology. . However, mathematics is known as a difficult and boring subject because the learning process is only focused on textbooks as the main guide. Therefore, other learning models are needed that can increase interest in learning, such as the brain based learning model. The aim of this research is to improve student learning outcomes in the field of mathematics on data collection and presentation material using a brain based learning model using used goods. This type of research is classroom action research using a qualitative deductive method by taking data from 20 people from grade 5 elementary school students. The results of the research show that the brain based learning model is proven to increase learning outcomes by up to 25% with an average initial learning score of 60 to 81 with completeness. classic increased 60%.